PENELITIAN DRAINASE JALAN RAYA (STUDI KASUS RUAS JALAN PALIMANAN JATIBARANG KM - Petrus Syariman (Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2009)
Highways are often damaged by excessive water content below road surface. The road section betweenPalimanan - Jatibarang, West Java is an area often flooded particularly at left and right sides of road. Toprevent floods, a study on these ditches had been implemented to determine the dimension of a ditchproportional with hydrological conditions in its vicinity. The method applied in this study had been themapping of detailed highway situation, rainfall intensity analysis, design flood analysis, and flow dischargesimulation using a HEC-HMS model. Study results showed that flow discharge passing through the out-letdrainage is 3.88 m3/sec and 6.29 m3/sec respectively, for a return period of two and five years. With a flowvelocity assumption of 1.2 m/sec and a cross sectional area of out-let drainage on site of 3.19 m2, inundationtime at vicinity of out-let is respectively four hours for a return period of two years, and six and half hours for areturn period of five years. The average cross sectional dimension recommended for a return period of twoyears is 1.36m x 2.0m, and for a return period of two years, 2.0 m x 2.0 m.